Undeniably Difficult: Extradition and Genocide Denial Laws - Dylan Fotiadis (Washington University Global Studies Law Review, 2018)
Genocide denial, increasingly common in the cyber world, is outlawed in several nations globally in an effort to suppress bigotry and harmful historical revisionism. Genocide denial is legal, however, in the United States, Canada, and the United Kingdom. Therefore, a legal conflict arises when a defendant facing genocide denial charges in one nation flees to or resides in a non-prosecuting nation: should respect for free speech or diplomacy prevail? Little material has been written on this matter, but with the rise of the internet as an anonymous means of communication, it is likely that this scenario will be increasingly common in the future. This note proposes that, in order to preserve First Amendment protections of free speech within its borders, but also prevent the United States from becoming a denialist safe harbor, the U.S. immigration system should strictly scrutinize the entry and admission of genocide deniers.
Keywords: extradition; genocide; genocide denial; cyber; first amendment; safe harbor